2015
DOI: 10.15436/2741-0598.15.005
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking MKP-­1 and MKP-­5 Reveal Hierarchical Regulation of Regenerative Myogenesis

Abstract: The relative contribution of the MAP kinase phosphatases (MKPs) in the integration of MAP kinase-dependent signaling during regenerative myogenesis has yet to be fully investigated. MKP-1 and MKP-5 maintain skeletal muscle homeostasis by providing positive and negative effects on regenerative myogenesis, respectively. In order to define the hierarchical contributions of MKP-1 and MKP-5 in the regulation of regenerative myogenesis we genetically ablated both MKPs in mice. MKP-1/MKP 5-deficient double-knockout (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…More recently, the study of DUSP1 −/− / DUSP10 −/− double knockout (DKO) mice revealed a severe impairment in muscle regeneration. Satellite cells, the precursors of muscle cells, were less proliferative and DKO mice had increased inflammation at sites of injury suggesting that the positive regulation of myogenesis by DUSP1 /MKP-1 is dominant over negative regulation by DUSP10 /MKP-5 [ 80 ]. Despite the fact that they share common substrates in JNK and p38 it is clear that these two MKPs regulate distinct signalling events.…”
Section: The Inducible Nuclear Mkpsmentioning
confidence: 99%
“…More recently, the study of DUSP1 −/− / DUSP10 −/− double knockout (DKO) mice revealed a severe impairment in muscle regeneration. Satellite cells, the precursors of muscle cells, were less proliferative and DKO mice had increased inflammation at sites of injury suggesting that the positive regulation of myogenesis by DUSP1 /MKP-1 is dominant over negative regulation by DUSP10 /MKP-5 [ 80 ]. Despite the fact that they share common substrates in JNK and p38 it is clear that these two MKPs regulate distinct signalling events.…”
Section: The Inducible Nuclear Mkpsmentioning
confidence: 99%
“…MKP-5-deficient mice exhibited increased muscle stem cell proliferation and differentiation and consequently improved myogenesis. When a mouse model of Duchenne muscular dystrophy was generated to lack the expression of MKP-5, it was found that dystrophic muscle disease, including the development of fibrosis, was attenuated (19,31,32). These observations suggested the involvement of MKP-5 in skeletal muscle fibrosis.…”
Section: L684mentioning
confidence: 99%
“…MKP-5 is highly expressed in skeletal muscle and is differentially regulated in response to specific stimuli such as cellular injury [ 4 , 13 , 14 ]. Our group has demonstrated that MKP-5 is an essential negative regulator of SC proliferation and differentiation [ 4 , 58 ]. SCs endow skeletal muscle with its highly regenerative capacity, and the process of regeneration in response to injury is orchestrated by synchronizing the activation of various cellular responses [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MAPKs have also been shown to be involved in regulating myofiber survival [ 61 , 62 ]. In skeletal muscle, p38 MAPK and JNK are negatively regulated by MKP-5, which contributes to the maintenance of myofiber homeostasis [ 4 , 58 ]. During muscle regeneration, MKP-5 is downregulated, thereby promoting p38 MAPK/JNK signaling and subsequent repair of damaged muscle [ 4 ].…”
Section: Discussionmentioning
confidence: 99%